A micro-IRRAS study of lubricant degradation under thin film conditions - Cann,PM; Spikes,HA (2005)
This paper studies lubricant degradation in a rubbing contact under thin film conditions. Friction tests have been carried out in an MTM test device using a steel ball/steel disc configuration. The tests were run with a small amount of lubricant present. At the end of the test the disc was retained for analysis. Micro-reflection FTIR spectroscopy was used to analyse the lubricant chemistry within and close to the rubbed track. The technique offers a more direct method for studying lubricant degradation products during rubbing. The results are compared to those from more conventional experimental methods. Copyright © 2005 by ASME.